Meningkatan Sarana Usaha Pengelolaan Sampah Plastik- Bank Sampah Sapujagad Kabupaten Magetan - astirin, okid parama; Hadi, Syamsul; Suryanto, Suryanto; Amanto, Bambang Sigit; Nugraha, Setya (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Waste both organic waste and inorganic waste is one of the threats and serious problems being faced in urban areas in Magetan. Milang Asri landfill (TPA) Magetan has experienced overload capacity conditions. The active role of the community in the form of Waste Bank and KSM (Community Self Help Group) in managing 3 R waste (Temporary waste disposal site) is needed to reduce the volume of waste piled up in Milangasri landfill. One alternative to solving the waste problem is to join the program of the Magetan